2016
DOI: 10.1097/md.0000000000004718
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors (GISTs) and second malignancies

Abstract: Several evidences showed that patients with gastrointestinal stromal tumors (GISTs) develop additional malignancies. However, thorough incidence of second tumors remains uncertain as the possibility of a common molecular pathogenesis.A retrospective series of 128 patients with histologically proven GIST treated at our institution was evaluated. Molecular analysis of KIT and PDGFR-α genes was performed in all patients. Following the involvement of KRAS mutation in many tumors’ pathogenesis, analysis of KRAS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Our results provide further support to this, since only six of our cases carried mutations in c-KIT or PDGFRα, whereas the rest three cases proved to be negative for all of the investigated exons. The most frequently mutated exon was the c-KIT exon 11, concordantly with other studies 5,6,10,13 . One mutation in the exon 18 of the PDGFRα (D842V) is reported to be associated with resistance to imatinib 11,40 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results provide further support to this, since only six of our cases carried mutations in c-KIT or PDGFRα, whereas the rest three cases proved to be negative for all of the investigated exons. The most frequently mutated exon was the c-KIT exon 11, concordantly with other studies 5,6,10,13 . One mutation in the exon 18 of the PDGFRα (D842V) is reported to be associated with resistance to imatinib 11,40 .…”
Section: Discussionsupporting
confidence: 90%
“…Several studies reported high sporadic coincidence of GISTs and other neoplasms and described GISTs as "sentinel tumors" 13,21,50 . In the case of adjacent synchronous tumors, we speculate that the gastrointestinal adenocarcinoma provides a growth factor-rich microenvironment, which induces the development of GIST from the nearby Cajal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofibromatosis, in which GISTs are associated with multiple additional benign and malignant tumors [7,8]. In several single institution case series and reviews, patients with sporadic GIST are reported to have an increased incidence of synchronous or metachronous secondary neoplasms at rates from around 4.5% to 43% [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Pdgfrmentioning
confidence: 99%
“…The revolutionary survival increase of GIST patients is a key example of how the advancement in screening, diagnosis, treatment and follow up have increased the life expectancy of cancer patients and, consequently, how cancer survivors live long enough to develop second primary tumors. Rodriquenz et al[8] indeed suggested tumor important component of the clinical management and follow up of GIST patients, especially in the first years after GIST diagnosis. This is most important to highlight because, even today, many symptoms and new lesions in GIST patients are still misinterpreted.…”
mentioning
confidence: 99%